Hydrolysis of Carbonyl Sulfide in Binary Mixture of Ethylene Glycol and Water - Ronghua, Deng; Yingxin, Liu; Jianbin, Zhang; Wenyong, Li; Xionghui, Wei (Asian Journal of Chemistry, 2010)
The solubility and hydrolysis properties of carbonyl sulfide in binary mixture of ethylene glycol and water were studied as a function of composition. The use of an ethylene glycol aqueous solution can enhance the solubility and hydrolysis rate of carbonyl sulfide compared with that in pure water. The composition of the mixture with maximum hydrolysis rate varies with temperatures. The physicochemical properties including density, viscosity and surface tension as a function of composition at 308.15 K under atmospheric pressure as well as liquid-liquid equilibrium data on the temperature range from 308.15 to 318.15 K were also measured for the binary mixture.